Daya hasil beberapa varietas Kedelai unggul nasional di Distrik Manokwari Barat dan Sidey Provinsi Papua Barat - Agustinus Warbaal; Januarius Renwarin; Nouke L. Mawikere; Yohanis A. Mustamu (Cassowary, 2019)
This study aims to examine the yield of 5 national superior soybean varieties in two different locations and select high yielding varieties to be developed in West Papua Province. This research was conducted for four months, which was located in 2 places namely West Manokwari and Sidey District in West Papua Province. The study used a Randomized Block Design with the treatment of 6 varieties (5 national varieties and 1 local variety), which were repeated 4 times so that 24 experimental units per location were obtained. The data obtained were analyzed using analysis of variance (ANOVA) and if the treatment had a significant effect it was continued with the DMRT test at a 95% confidence level. The results showed that the varieties tested were highly significant for plant height, number of branches, total number of pods, number of empty pods, number of filled pods, weight of planting seeds, weight of seeds per plot, weight of corrected seeds, and weight of 100 dried seeds. The yield of 3 varieties suitable for development in West Papua Province are Rajabasa varieties 1.63 tons/ha, Burangrang 1.8 tons/ha, and Detam-2 2.35 tons/ha.